Preparation method of positive electrode material for sodium ion battery

By ball milling the manganese source and the sodium source and blowing the mixed gas into a high-temperature furnace for sintering, a stable sodium ion battery positive electrode material was prepared, which solved the problem of reduced battery life caused by the change of the valence state of manganese element and achieved further Long battery life and more stable battery performance.

CN117566801BActive Publication Date: 2025-02-25DONGGUAN XINDIAN ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311553907.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2025-02-25
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

During the charging and discharging process of sodium ion battery positive electrode material, manganese element is prone to undergo valence changes, resulting in crystal form changes and reducing the cycle life of the battery.

Method used

Using a preparation method of a positive electrode material for sodium ion batteries, the manganese source and sodium source are ball milled to 10μm particles, and blown in a high-temperature furnace with mixed gas (inert gas and air) to sinter the process to form a stable Positive electrode material.

Benefits of technology

Through this method, the service life of the positive electrode material in the battery is improved, and the impact of the addition of other elements on the battery performance is avoided.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps: ball-milling a manganese source and a sodium source to particles with an average particle size of 10 μm, and uniformly mixing the manganese source and the sodium source to obtain a mixture; adding the mixture to the furnace of a high-temperature furnace, blowing a mixed gas into the furnace, the mixed gas consisting of an inert gas and air, the volume ratio of the inert gas to the air being (5-9): (1-5), and the flow rate of the mixed gas being 50 m / s; starting the high-temperature furnace, turning the furnace upside down, the rotation speed of the furnace being 5 turns / h, and sintering for 8-12 hours after heating to 550-850°C, to obtain a positive electrode material. By blowing a mixed gas into the furnace of the high-temperature furnace, a high-speed mixed gas collides with a manganese source and a sodium source, so that in the synthesis process of the positive electrode material, in the growth process of the crystal, adjacent grains collide, thereby generating dislocations, thereby increasing the service life of the battery in the material, and at the same time, because no other elements are added, other battery properties are not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of positive electrode materials, and in particular to a method for preparing a positive electrode material for a sodium ion battery. Background Art

[0002] Sodium ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of sodium ions between the positive electrode and the negative electrode to work, similar to the working principle of lithium ion battery. Sodium ion battery has become a research hotspot of various research institutions because it uses sodium element to replace lithium element, and the source of sodium element material is wide and not affected by the international environment. Among the positive electrode materials of sodium ion batteries, transition metal oxides have gradually become the main materials used because of their simple preparation process and stable and reliable performance. Among them, the theoretical gram capacity of sodium manganese oxide material reaches 243mAh / g, becoming the most promising positive electrode material.

[0003] However, the manganese element in sodium manganese oxide has multiple valence states. During the charge and discharge process, the manganese element is prone to valence changes, resulting in changes in the crystal form. The traditional method is to add additives of other elements to it to make the crystal defective or dislocation, so that the valence state of manganese is not easy to change, and its life in the battery is improved. No matter what element is added, there will be a reduction in active substances, affecting the energy density, and other elements may affect other performances of the battery. Therefore, it is necessary to propose a new solution to improve the above problems. Summary of the invention

[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a method for preparing a positive electrode material for a sodium ion battery, which can effectively solve the problem that the elements in the existing sodium ion battery electrodes are prone to valence changes during the charge and discharge process, thereby causing changes in the crystal form and resulting in a reduction in the cycle life of the battery.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:

[0007] (1) ball-milling a manganese source and a sodium source into particles with an average particle size of 10 μm, and uniformly mixing the manganese source and the sodium source, wherein the molar ratio of the manganese source to the sodium source is 1:1, to obtain a mixture;

[0008] (2) adding the mixture obtained in step (1) into the furnace of a high-temperature furnace, and blowing a mixed gas into the furnace, wherein the mixed gas consists of an inert gas and air, the volume ratio of the inert gas to the air is (5-9):(1-5), and the flow rate of the mixed gas is 50 m / s;

[0009] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions / h, and heat to 550-850°C and sinter for 8-12 hours to obtain the positive electrode material.

[0010] As a preferred embodiment, the manganese source is manganese trioxide, and the sodium source is sodium carbonate.

[0011] As a preferred embodiment, the inert gas in step (2) is argon.

[0012] As a preferred solution, the furnace in step (2) is hourglass-shaped.

[0013] As a preferred solution, in step (2), the mixed gas is blown into the furnace in the middle of the furnace.

[0014] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0015] By blowing mixed gas into the furnace of the high-temperature furnace, the high-speed mixed gas collides with the manganese source and the sodium source, causing adjacent grains to collide during the synthesis of the positive electrode material and the growth of the crystal, thereby generating dislocations, thereby increasing the service life of the material in the battery. At the same time, since no other elements are added, other battery properties are not affected.

[0016] In order to more clearly illustrate the effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. DETAILED DESCRIPTION

[0017] The present invention discloses a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:

[0018] (1) The manganese source and the sodium source are ball-milled to particles with an average particle size of 10 μm, and the manganese source and the sodium source are evenly mixed, and the molar ratio of the manganese source to the sodium source is 1:1 to obtain a mixture. Specifically, the manganese source is manganese trioxide, and the sodium source is sodium carbonate.

[0019] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, and blow a mixed gas into the furnace, wherein the mixed gas consists of an inert gas and air, and the volume ratio of the inert gas to the air is (5-9):(1-5), the inert gas is argon, and the flow rate of the mixed gas is 50 m / s, wherein the furnace is shaped like an hourglass; the mixed gas is blown into the furnace in the middle of the furnace.

[0020] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions / h, and heat to 550-850°C and sinter for 8-12 hours to obtain the positive electrode material.

[0021] The following describes it in detail with reference to specific embodiments.

[0022] Example 1

[0023] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0024] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 5:5, and the flow rate of the mixed gas is 50m / s.

[0025] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 550° C. and sinter for 8 hours to obtain the positive electrode material.

[0026] Example 2

[0027] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0028] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 6:4, and the flow rate of the mixed gas is 50m / s.

[0029] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 550° C. and sinter for 8 hours to obtain the positive electrode material.

[0030] Example 3

[0031] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0032] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0033] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 550° C. and sinter for 8 hours to obtain the positive electrode material.

[0034] Example 4

[0035] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0036] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 8:2, and the flow rate of the mixed gas is 50m / s.

[0037] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 550° C. and sinter for 8 hours to obtain the positive electrode material.

[0038] Example 5

[0039] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0040] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 9:1, and the flow rate of the mixed gas is 50m / s.

[0041] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 550° C. and sinter for 8 hours to obtain the positive electrode material.

[0042] Example 6

[0043] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0044] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0045] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 600° C. and sinter for 8 hours to obtain the positive electrode material.

[0046] Example 7

[0047] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0048] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0049] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 700° C. and sinter for 8 hours to obtain the positive electrode material.

[0050] Example 8

[0051] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0052] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0053] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 750° C. and sinter for 8 hours to obtain the positive electrode material.

[0054] Example 9

[0055] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0056] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0057] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 800° C. and sinter for 8 hours to obtain the positive electrode material.

[0058] Example 10

[0059] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0060] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0061] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 850° C. and sinter for 8 hours to obtain the positive electrode material.

[0062] Embodiment 11

[0063] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0064] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0065] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 750° C. and sinter for 9 hours to obtain the positive electrode material.

[0066] Example 12

[0067] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0068] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0069] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 750° C. and sinter for 10 hours to obtain the positive electrode material.

[0070] Example 13

[0071] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0072] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0073] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 750° C. and sinter for 11 hours to obtain the positive electrode material.

[0074] Embodiment 14

[0075] (1) Manganese trioxide and sodium carbonate are ball-milled to an average particle size of 10 μm, and the manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide to sodium carbonate is 1:1, to obtain a mixture.

[0076] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, the furnace is in the shape of an hourglass, and blow a mixed gas into the middle of the furnace, the mixed gas consists of argon and air, the volume ratio of argon to air is 7:3, and the flow rate of the mixed gas is 50m / s.

[0077] (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 750° C. and sinter for 12 hours to obtain the positive electrode material.

[0078] Comparative Example 1

[0079] Commercially available sodium manganese oxide positive electrode material was used.

[0080] Comparative Example 2

[0081] (1) Manganese trioxide, sodium carbonate and aluminum oxide are ball-milled to an average particle size of 10 μm, and manganese trioxide and sodium carbonate are uniformly mixed, wherein the molar ratio of manganese trioxide, sodium carbonate and aluminum oxide is 1:1:1, to obtain a mixture.

[0082] (2) Add the mixture obtained in step (1) into the furnace of a high-temperature furnace, start the high-temperature furnace, heat it to 750° C., and sinter it for 11 hours to obtain a positive electrode material.

[0083] The positive electrode materials of the above-mentioned multiple embodiments and comparative examples are made into positive electrode sheets, the positive electrode material, carbon nanometers, PVDF, and NMP are mixed in a weight ratio of 94:1:5:50 and stirred evenly, coated on an aluminum foil with a thickness of 12 μm, dried, rolled, and cut to obtain a positive electrode sheet for a sodium ion battery; it is wound with a hard carbon negative electrode and a diaphragm, injected with 1.2 mol / L sodium hexafluorophosphate electrolyte, sealed, and formed to obtain a finished battery, and the finished battery is subjected to a 1C cycle life test, and the test results are shown in the following table.

[0084] Example 1C cycle life times Example 1 264 Example 2 272 Example 3 286 Example 4 280 Example 5 281 Example 6 289 Example 7 293 Example 8 296 Example 9 290 Example 10 286 Embodiment 11 300 Example 12 305 Example 13 320 Embodiment 14 317 Comparative Example 1 212 Comparative Example 2 231

[0085] Table 1.

[0086] It can be seen from the above data that the new process significantly increases the life of the battery. The best effect is achieved when the volume ratio of argon to air is 7:3. Because argon has a large density and a strong impact force, nitrogen can be used as an inert gas, but the effect is not good. Other high-density inert gases can also be used, but the cost is high. At the same time, when the proportion of argon is too high, the amount of air blown in is insufficient, and sufficient oxygen is required in the synthesis reaction, which will lead to slow crystal growth and the crystal cannot grow rapidly toward the same crystal plane, resulting in poor particle density of the generated positive electrode material. In addition, when the sintering temperature is 750°C and the sintering time is 11h, the performance of the obtained positive electrode material is the best. In Comparative Example 2, alumina is used as an additive to improve the battery life, but the improvement effect is limited and not optimal. The main reason is that when alumina is added to the reaction system, the mixture will be difficult to mix evenly, and other elements are introduced into the reaction system, resulting in the positive electrode material being doped with a small amount of impurities, which in turn causes damage to the battery and affects the cycle life of the battery.

[0087] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The following steps are included: (1) ball-milling a manganese source and a sodium source to particles with an average particle size of 10 μm, and uniformly mixing the manganese source and the sodium source, wherein the molar ratio of the manganese source to the sodium source is 1:1, to obtain a mixture, wherein the manganese source is manganese trioxide, and the sodium source is sodium carbonate; (2) adding the mixture obtained in step (1) into the furnace of a high-temperature furnace, and blowing a mixed gas into the furnace, wherein the mixed gas consists of an inert gas and air, and the volume ratio of the inert gas to the air is (5-9):(1-5), the flow rate of the mixed gas is 50 m / s, and the inert gas is argon; (3) Start the high-temperature furnace, turn the furnace upside down, rotate the furnace at a speed of 5 revolutions per hour, and heat to 550-850°C and sinter for 8-12 hours to obtain the positive electrode material.

2. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The furnace in step (2) is in the shape of an hourglass.

3. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the step (2), the mixed gas is blown into the furnace at the middle of the furnace.

Citation Information

Patent Citations

  • Quintuple layered oxide cathode material for sodium ion battery and preparation method of quintuple layered oxide cathode material

    CN105161703A

  • Method for preparing multielement positive pole material for sodium-ion batteries

    CN105576229A